Comparative Anatomical Studies On Rib Cages Of Kite (Millvus Migrans) And Crow (Corvus Splendens) (Applied Biological Research, 2015)
A study was conducted on the rib cage of kite and crow collected by  maceration process. The rib cage of kite and crow comprised of seven and  six pairs of true ribs, respectively. A single pair of floating rib was found in  both the species. The vertebral part of all true ribs, except the last one, in  both birds was featured with uncinate process. The floating rib of crow  unveiled a rudimentary uncinate process. The vertebral part of ribs of kite,  except 6th rib, revealed the presence of pneumatic foramina. True and  floating ribs of crow lacked pneumatic foramen in its vertebral parts. The  medialsurface ofallsternal ribs of kite, except 7th one, had a well-developed  pneumatic foramen. However, pneumatic foramen was absent in 3rd and  7th sternal ribs of crow. The last pair of ribs in both the species was  attached to the preceding rib. The remaining pairs of ribs were in  articulation with sternum. It may be concluded that the rib cage of kite is  highly pneumatised as compared to that of crow. The greater number of  pneumatic foramen in kite might be an adaptation feature to cope up with  the larger sized organs during flight.
Keywords: Anatomy; crow; kite; rib cage; uncinate process